POLA PELAKSANAAN BIMBINGAN KLASIKAL SECARA CYBER MENGGUNAKAN MEDIA PODCAST SEBAGAI UPAYA MENINGKATKAN MOTIVASI BERPRESTASI MAHASISWA UIN ANTASARI BANJARMASIN PASCA PANDEMI COVID-19 - Erlita Budiarti; Raifa Ermila Aina (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
During the Covid-19 pandemic, it's requires all students to do distance learning, the large number of assignments received make students depressed and anxious so that the substance of productivity in learning decreases, all forms of platforms are available starting from whatsapp groups, google classroom, to zoom and skype. Interactive learning armed with learning motivation makes students need services that are not burdensome to students and adjusted for efficient time, the need for counseling guidance services used in the learning process, classical guidance services are allocated in the new reality era, on internet use so that counselor's are required to be skilled in providing guidance. This research uses a descriptive qualitative approach. This study aims to determine the extent of the effectiveness of podcasts in providing learning motivation, after this research was carried out supported by secondary data and primary data. After doing research through google research from and online interviews. It can be concluded that podcast media is an alternative best partices media as an implementation of longdistance classical guidance.